Factors affecting mortality of neonatal sepsis in Moewardi Hospital, Surakarta - Yulidar Hafidh; Dwi Hidayah; Sunyataningkamto Sunyataningkamto (Paediatrica Indonesiana, 2007)
Background Mortality of neonatal sepsis is still a significantproblem. It might be affected by many factors.Objective The purpose of this study was to determine factorswhich affect mortality of neonatal sepsis at neonatal ward ofMoewardi Hospital, Surakarta.Methods Data of neonatal sepsis was obtained from medicalrecords at the neonatal ward of Moewardi Hospital from December2004 to November 2005. We recorded data from 97 neonatalsepsis consisted of 46 male and 52 female babies. Statisticalanalysis had been performed using univariate Chi-square andmultivariate multiple logistic regression analysis.Results Overall neonatal sepsis mortality was about 40%. Therewere no significant difference in factors associated with mortalityof neonatal sepsis such as gender (OR=0.44; 95% CI 0.19;1.014),referral patients (OR=1.61; 95% CI 0.195;.014), and bacterialgrowth culture (OR=1.96; 95% CI 0.856;4.44), except for birthweight which affected mortality (OR=6.29; 95% CI 2.57;15.42).Conclusion Birth weight affects mortality of neonatal sepsis inMoewardi Hospital. Patients with positive bacterial growth culturehas two times higher risk of death, however, it is not statisticallysignificant.